Preventive Effect of Gamma-Oryzanol on Physiopathological Process Related to Nonalcoholic Fatty Liver Disease in Animals Submitted to High Sugar/Fat Diet - Francisqueti-Ferron, Fabiane Valentini [UNESP] (2022)
Nonalcoholic fatty liver disease (NAFLD) is the main cause of liver disease. The physiopathological processes involved in the disease are metabolic syndrome (MetS) components (central obesity, dyslipidemia, insulin resistance/type 2 diabetes, hypertension), genetic, and dietary factors, including unsaturated fats and sweetened beverages, which are able to lead to inflammation and oxidative stress, conditions associated with progression and severity of NAFLD. Gamma-oryzanol (γOz) is a nutraceutical obtained from rice brain oil with many benefits to health, from immunological to metabolic. The aim of this study is to test the preventive effect of γOz on the physiopathological process related to nonalcoholic fatty liver disease in animals submitted to high sugar/fat diet. Male Wistar rats (±187 g) were randomly divided into four experimental groups to receive: control diet (C, n = 6), control diet plus γOz (C + γOz, n = 6), high sugar/fat diet (HSF, n = 6), or high sugar/fat diet plus γOz (HSF + γOz, n = 6) during 30 weeks. HSF groups also received water plus sucrose (25%). γOz was added to diets to reach 0.5% of final concentration. The HSF group presented MetS, liver inflammation and oxidative stress, and micro and macrovesicular steatosis. HSF plus γOz was protected against these changes. It is possible to conclude that gamma-oryzanol was effective in modulating the physiopathological process related to nonalcoholic fatty liver disease in animals submitted to a high sugar/fat diet.